Learners’ experiences of the journey to school in Komenda-Edina-Eguafo-Abrem municipality - Ayisi Augustine Mensah (University of Cape Coast, 2023)
The success of education and training which is typically tied to productivity and economic growth is incomplete minus the experience’s learners’ face on their journey to school. Attention to access to quality education and improved learning outcomes seems to miss this all-important consideration. Thus, this study explored learners’ experiences of their journey to school. The study draws on drawing activity from learners and semi-structured interview guides within the context of phenomenological case study design to explore the phenomenon. Eighteen participants purposively selected from a remote basic school in the Komenda-Edina-Eguafo-Abrem Municipality formed the sample. Thematic analysis was carried out to situate the findings. Learners' journey to school experiences were influenced by factors like time, safety concerns, socialization, and route options. They exercise agency through planning, time management, safety strategies, hygiene, and advocating for neighborhood changes. Learners' persistence in completing school stems from academic achievement, institutional support, aspirations, and the recognition of education as a lifechanging tool. The study concludes that learners face a complex journey to school experiences, requiring them to showcase their capacity to achieve their education goals. Based on these findings and conclusion drawn from the study, it is recommended that education policy makers and stakeholders put up measures such as infrastructure improvement that will ensure safe and smooth journey to school to enhance learner’s completion and success.
xiv,157p:,ill
Keywords: Agency Children agency Experiences Journey to school Learners Persistence